Analysis on digital image watermarking using DCT-DWT techniques / Rabi’atul Adawiyah Tarmizi - Tarmizi, Rabi’atul Adawiyah (2020)
In recent years, digital images are used in various platforms by all means of purpose by people and also creators. The data also can be easily copied or altered, and anyone with a computer can create the forgeries too. The work on digital watermarking of images has introduced several strategies over the years, either using spatial or transform domain. Nevertheless, as the technologies are evolving, the digital images become more vulnerable towards illegal threats such as illegal duplication and removal attack without the creator's consent and the approach or watermarking techniques used are still aren't robust enough to secure the digital images hence, more approach can be applied to make it more secure. So to tackle the problem, the combined or hybrid of Discrete Cosine Transform (DCT) and Discrete Wavelet Transform (DWT) watermarking techniques are developed in this project to analyses and evaluate the performance of the proposed techniques. The techniques are developed and applied to the image according to the watermarking process, which started from the embedding process until the watermark extraction. Based on the results, the purposes of the project has been achieved as the watermarking techniques showed a good performance in terms of imperceptibility and robustness, measured by the two measuring parameter which are the Peak Signal-to-Ratio (PSNR) and correlation factor values.